Online Quiz in English Assessment at Islamic University - Pratama, Aryawira (Universitas Islam Lamongan, 2024)
This research investigates the impact of online quizzes on student engagement and learning outcomes in English courses at an Islamic university in Jambi. Utilizing a quantitative approach and survey design, the research employed a questionnaire with 20 positive statements across four themes: ease of use, interactivity and engagement, learning effectiveness, and user satisfaction. The sample consisted of 150 students who completed the survey. Results revealed that 80% of respondents expressed positive feedback across all themes. Students reported that online quizzes are easy to use, engaging, and effective in enhancing their understanding and retention of course material. The interactive features, such as instant feedback and gamification, were particularly appreciated for maintaining motivation. Overall, the high level of student satisfaction highlights the effectiveness of online quizzes as a supplementary educational tool. These findings suggest that integrating online quizzes into the curriculum can significantly improve student engagement and learning outcomes. The research underscores the broader potential of educational technology in transforming learning experiences and emphasizes the need for continuous refinement and innovation in digital learning tools.